THE ARKAN AL-USRAH CONCEPT ASPIRES TO FOSTER UNITY AMONG SOCIETY - Nur Bakri Abd Hamid; Izzul Syahmi Zukepli; Hazrul Hizam Karim (Journal of Islamic, Social, Economics and Development, 2024)
The Islamic values advocate for a peaceful and cooperative coexistence and solidarity among many religions and nations. Historical instances, such as the Prophet's hospitable reception in Madinah and the tactical application of Muakhah, illustrate the efficacy of these principles in addressing societal problems and promoting communal harmony, which were subsequently adapted by Hasan al-Banna and his al-Ikhwan al-Muslimin movement to suit the circumstances in Egypt. The challenges surrounding unity in Malaysia are complex and diverse, reflecting the nation's distinctive historical, cultural, and socio-economic circumstances. To address these challenges, it is necessary for the government, civil society, and individuals to collaborate in order to foster inclusivity, comprehension, and reverence among all Malaysians. This article employs library research methodologies to collect a diverse range of ideas, facts, research findings, and expert opinions, along with relevant analysis. The collected data were then examined using descriptive content analysis. The research findings emphasize the importance of unity and the implementation of the arkan al-Usrah idea in order to enhance the well-being and inclusiveness of a society. It is evident that Hasan al-Banna's perspectives on arkan al-Usrah remain relevant and consistent with the teachings of the Prophets, both in terms of their narrative and practical application, in order to fortify and unite the Muslim ummah.